2011
DOI: 10.1162/jocn.2010.21443
|View full text |Cite
|
Sign up to set email alerts
|

Slow Fluctuations in Attentional Control of Sensory Cortex

Abstract: Top-down control of visual sensory cortex has long been tied to the orienting of visual spatial attention on a rapid, moment-to-moment basis. Here, we examined whether sensory responses in visual cortex are also modulated by natural and comparatively slower fluctuations in whether or not one is paying attention to the task at hand. Participants performed a simple visual discrimination task at fixation as the ERPs to task-irrelevant probes in the upper visual periphery were recorded. At random intervals, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
245
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 213 publications
(275 citation statements)
references
References 49 publications
(86 reference statements)
25
245
4
1
Order By: Relevance
“…Likewise, one might argue that the reduction in P1 amplitude for the visual probes following "self " cues could reflect cue-dependent shifts in more general attentional states rather than a specific narrowing of visual spatial attention. For instance, when we naturally drift into a mind wandering state, where oneʼs thoughts become more internally focused, there is a concomitant reduction in the degree of sensory processing in both the visual and auditory domains (Kam et al, 2011)-effects directly analogous to what we observed in our P1 data. Accordingly, if "self" cues triggered a greater degree of internal reflection relative to "other" cues, then that could explain our P1 results from Experiment 2.…”
Section: Discussionsupporting
confidence: 74%
“…Likewise, one might argue that the reduction in P1 amplitude for the visual probes following "self " cues could reflect cue-dependent shifts in more general attentional states rather than a specific narrowing of visual spatial attention. For instance, when we naturally drift into a mind wandering state, where oneʼs thoughts become more internally focused, there is a concomitant reduction in the degree of sensory processing in both the visual and auditory domains (Kam et al, 2011)-effects directly analogous to what we observed in our P1 data. Accordingly, if "self" cues triggered a greater degree of internal reflection relative to "other" cues, then that could explain our P1 results from Experiment 2.…”
Section: Discussionsupporting
confidence: 74%
“…P1 ERP contrasts were evaluated with repeated-measures ANOVA (factors Task Focus [FOCUS] and Location [LOC]) of peak deflections over parietal and parieto-occipital electrodes with corresponding 10-20 equivalents (GSN channel 61 (P1), 78 (P2), 60 (PO3), 85 (PO4)), where P1 amplitude tends to be maximal (Kam et al, 2011;Handy & Khoe, 2005;Handy, Soltani, & Mangun, 2001). The time window for detecting peak amplitude of the P1 component was 50-150 msec (e.g., Klimesch, Hanslmayr, Sauseng, Gruber, & Doppelmayr, 2007).…”
Section: P1 Event-related Potentialsmentioning
confidence: 99%
“…One well-documented aspect of these experiences (often referred to as mind-wandering or task-unrelated thought) is that their occurrence corresponds to periods of time when external input is neglected (for reviews, see Smallwood, 2013;Schooler et al, 2011). Evidence using a variety of measures of task-unrelated thought and using a variety of different measures of cortical processing indicates that these periods are accompanied by an attenuation of the processing of perceptual input, a phenomenon that has been termed "perceptual decoupling" (Barron, Riby, Greer, & Smallwood, 2011;Kam et al, 2011;Smallwood, Brown, Baird, & Schooler, 2011;Smallwood, Brown, Tipper, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the rate of mindwandering for each participant via subjective reports of participants current attentional state (on-task versus mind-wandering), collected at regular but unpredictable intervals (see below). The SART is a widely-used paradigm in mind-wandering studies, where participants are required to respond to frequently presented targets, while inhibiting responses to infrequent targets (e.g., Kam et al, 2011;Smallwood et al, 2008). The SART is thought to measure sustained attention -which is influenced by the moment-to-moment efficacy of attentional control mechanisms (Manly, Robertson, Galloway, & Hawkins, 1999).…”
mentioning
confidence: 99%